2016
DOI: 10.1097/sla.0000000000001246
|View full text |Cite
|
Sign up to set email alerts
|

The Incremental Risk of Coronary Stents on Postoperative Adverse Events

Abstract: Surgery after coronary stent placement is associated with an approximate 2% absolute risk for postoperative MI but no difference in mortality compared with nonstented matched controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
31
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 24 publications
1
31
0
8
Order By: Relevance
“…However, patients with stents had a higher risk of adverse cardiac events within the 30-day post-operative period. 227 The incremental risk did not vary by stent type. 227 In both studies, roughly 50% of patients underwent stenting because of ACS and no incremental risk was observed in this higher risk population as compared to stable CAD patients.…”
Section: Elective Non-cardiac Surgery In Patients On Dual Antiplatelementioning
confidence: 95%
See 2 more Smart Citations
“…However, patients with stents had a higher risk of adverse cardiac events within the 30-day post-operative period. 227 The incremental risk did not vary by stent type. 227 In both studies, roughly 50% of patients underwent stenting because of ACS and no incremental risk was observed in this higher risk population as compared to stable CAD patients.…”
Section: Elective Non-cardiac Surgery In Patients On Dual Antiplatelementioning
confidence: 95%
“…227 The incremental risk did not vary by stent type. 227 In both studies, roughly 50% of patients underwent stenting because of ACS and no incremental risk was observed in this higher risk population as compared to stable CAD patients. Therefore, a minimum of 1 month of DAPT should be considered, independently of the type of implanted stent (i.e.…”
Section: Elective Non-cardiac Surgery In Patients On Dual Antiplatelementioning
confidence: 95%
See 1 more Smart Citation
“…We compared cohorts of patients with metastatic cancer who did and did not receive chemotherapy, matchedby key demographic and health characteristics and controlling for important unmatched characteristics, to estimate the difference in risk of hospitalization likely attributable to chemotherapy. This approach, consistentwithpreviousstudiesoftreatmentcomplications [41][42][43] and with the epidemiologic concept of attributable or excess risk, 44 does not require direct attribution of each hospitalization to a specific cause, a task that is challenging even with detailed clinical information. 45 However, there may have been residual confounding by unmeasured factors, such as pretreatment symptom burden, performance status, and functional status, other risk factors for treatment-related adverse effects, patient preferences, or physician recommendations.…”
mentioning
confidence: 73%
“…However, large observational studies have shown that the highest risk for major adverse cardiac events (MACE) following surgery after recent PCI is confined to the first 6 months after stent placement with no significant difference in the rate of postoperative MACE by stent type. 25 Given that stent types do not explain the inverse relationship between time from PCI and perioperative MACE risk, we explored whether the indication for stent placement may provide additional information regarding the risk of MACE after noncardiac surgery.…”
mentioning
confidence: 99%